Bounding box based distributed search localization algorithm for WSN - Ying-biao YAO; Rong ZENG; Zhi-qiang YI (Tongxin xuebao)
A bounding box based distributed full search localization algorithm for WSN(wireless sensor networks)was proposed.Firstly,the coordinates and distances of neighbor nodes were obtained by ranging.Secondly,the possible node position area was determined based on bounding box method.Finally,the area was meshed and the full search method was employed to search the best estimation point,whose coordinates are the node’s localization coordinates.In real WSN,the algorithm need run several rounds to obtain node’s localization coordinates by stepwise refinement.Simulation results show that the proposed algorithm achieves the comparable performance with other up-to-date complex localization algorithms.